2015
DOI: 10.1016/j.ntt.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Low and moderate prenatal ethanol exposures of mice during gastrulation or neurulation delays neurobehavioral development

Abstract: Human and animal studies show significant delays in neurobehavioral development in offspring after prolonged prenatal exposure to moderate and high ethanol doses resulting in high blood alcohol concentration (BECs). However, none have investigated the effects of lower ethanol doses given acutely during specific developmental time periods. Here, we sought to create a mouse model for modest and circumscribed human drinking during the 3rd and 4th weeks of pregnancy. We acutely treated mice during embryo gastrulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 75 publications
3
9
0
Order By: Relevance
“…Whereas we were able to document phenotypic variation in locomotor behaviors that depend on sensorimotor integration among 39 DGRP lines, this sample did not provide enough power for GWA analysis. Our study also did not identify variants in genes of the insulin signaling pathway associated with variation in ethanol sensitivity in the DGRP, but instead identified a wide range of developmental genes, in line with previous cell-based or animal model studies ( Mandal et al 2015 ; Schambra et al 2015 ; Fish et al 2017 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Whereas we were able to document phenotypic variation in locomotor behaviors that depend on sensorimotor integration among 39 DGRP lines, this sample did not provide enough power for GWA analysis. Our study also did not identify variants in genes of the insulin signaling pathway associated with variation in ethanol sensitivity in the DGRP, but instead identified a wide range of developmental genes, in line with previous cell-based or animal model studies ( Mandal et al 2015 ; Schambra et al 2015 ; Fish et al 2017 ).…”
Section: Discussionsupporting
confidence: 84%
“…Rodent models have been used to examine morphological and neurological changes that occur following alcohol exposure, but the mechanisms of those effects are still unclear ( Kleiber et al 2011 ; Kleiber et al 2012 ; Schambra et al 2015 ; Marquardt and Brigman 2016 ; Saito et al 2016 ). Damage to the heart, brain and skeleton in response to prenatal alcohol exposure has been documented in animal models ( Cavieres and Smith 2000 ; Debelak and Smith 2000 ; Su et al 2001 ; Smith et al 2014 ; Sarmah and Marrs 2017 ).…”
mentioning
confidence: 99%
“…As mentioned in the introduction, we opted to use ethanol doses that reflect ethanol concentrations experienced by mammalian fetuses during development, which yielded in an anxiolytic phenotype. We acknowledge that different ethanol doses could potentially yield a different phenotype under this same exposure period, as it has occurred with mice and zebrafish during different points of development [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown evidence for delayed sensorimotor development (Endres et al, 2005, Schambra et al, 2015), altered exploratory behavior (Endres et al, 2005) impaired spatial learning or memory during adolescence or adulthood (Summers et al, 2006, Incerti et al, 2010, Minetti et al, 1996, Summers et al, 2008), suggesting altered hippocampal function, but others have not (Sadrian et al, 2014). The research described herein was designed to further understand the consequences of neurulation alcohol exposure by examining a comprehensive battery of behavioral tests in adolescent male and female C57 mice that were exposed to acute alcohol injections on GD8, the beginning of neurulation.…”
Section: Introductionmentioning
confidence: 99%